Role of Sling Tuina Exercise Technique in Improving Paraspinal Muscle Asymmetry in Patients with Adolescent Idiopathic Scoliosis - LIU Min; MA Zhaoshui; XU Qiangqiang; LI Li (康复学报)
ObjectiveTo investigate the impact of technique of sling exercise with Tuina therapy on improving paravertebral muscle asymmetry in patients with adolescent idiopathic scoliosis (AIS).MethodsA total of 88 patients with AIS who met the inclusion criteria and received treatment at the Rehabilitation Department of the Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine from October 2021 to August 2023 were recruited for this study. They were randomly divided into control group and experimental group, with 44 cases in each group. Routine rehabilitation training was performed in the control group with reference to the German Schroth scoliosis three-dimensional corrective therapy, including manipulation to relax the concave side of the paraspinal muscles, "hip bridge", and "small swallow fly" and other strength exercises. Schroth gymnastics included "muscle column", "rotational sitting movement", "stretching exercise" with angular breathing. The experimental group was treated with sling Tuina exercise technique which mainly included adjusting the position of the spine to restore the neutral position, the methods of plucking, pressing and pushing and other techniques to act back and forth on the Governor vessel, bladder meridian and the convex-concave side of the paravertebral muscle dialectical tonifying and reducing therapy, neutral position control training in supine, prone and lateral position, trunk flexion, extension, rotation and lateral flexion closed chain movement training with the assistance of sling equipment. Before treatment and after 4 weeks of treatment, the surface electromyography (sEMG) was used to measure the paraspinal muscles of the patients during standing weight-bearing position, and the root mean square (RMS) was calculated and analyzed through the included software, and the paraspinal muscle symmetry index was calculated (PMSI=RMSconvex/RMSconcave); Cobb's angle was used to assess the severity of the patients' scoliosis; and the angle of trunk rotation (ATR) was used to assess the degree of rotation of the trunk.ResultsBefore treatment, the PMSI values, Cobb's angle, and ATR values of the two groups were compared, and the differences were not statistically significant (P>0.05). After 4 weeks of treatment, the PMSI values of the experimental group was 1.08 (1.04, 1.14), the Cobb's angle was 5 (2, 9)°, and the ATR value was 2 (1, 3)°, while the PMSI value of the control group was 1.12 (1.09, 1.17), the Cobb's angle was 8.5 (6, 10)°, and the ATR value was 2 (2, 3)°. The intra-group comparison results showed that the Cobb's angle and ATR values decreased in both groups after treatment (P<0.05), and PMSI values were closer to 1 (P<0.05). The intra-group comparison results showed that the improvement of PMSI value and Cobb's angle in the experimental group was better than that in the control group after treatment, and the PMSI value was closer to 1 in the experimental group (P<0.05), and the Cobb's angle was significantly lower (P<0.05); however, there was no statistically significant difference of the ATR value between the two groups after treatment (P>0.05).Conclusiontechnique of sling exercise with Tuina therapy can effectively improve the asymmetry of paravertebral muscles and achieve the orthopedic purpose of reducing the Cobb's angle and trunk rotation angle of patients, which is recommended for clinical application.